A continuous-discontinuous deformation analysis method for simulating the progressive failure process of riverbanks. (October 2022) - Xu, Dongdong; Lu, Bo; Cheng, Yonghui; Zhu, Jiebing; Wang, Bin
Abstracts: River scouring is the primary cause of impulsive riverbank failure. Its direct effect is to cause catastrophic changes in the structure of the riverbank slope, which then leads to riverbank collapse. However, its internal evolution mechanism is unclear. To solve this problem, a continuous-discontinuous deformation analysis method that can reveal the evolution mechanism has been developed based on the Discontinuous Deformation Analysis (DDA) method. It discretizes the soil into Voronoi-shaped sub-blocks, forces the displacement coordination of the continuous medium through the defined bar element between the sub-blocks, and simulates the evolution from continuum to discontinuum through the bar element failure. At the same time, the open-close iteration algorithm is still used to deal with the contact between the real block boundaries and there is no need to judge the contact between sub-blocks. Then, for the first time, a generalized model of riverbank collapse caused by flow erosion is built, the entire failure process is simulated, and the effects of different soil strengths and slope ratios on the failure mode are discussed. The results indicate that it is insufficient to explain the mechanism of riverbank collapse only by using the concept of circular slip failure of a traditional soil slope.